(untitled) (Iris Journal of Scholarship, 2019)
This essay contends the introduction to Croft Middle School in Nashville based on online research and interviews. The author focuses more on the student population school-wide support for English Language Learners, and the learning environment. From the school visit, the author noticed the ESL classroom decoration was very creative and attractive, and it was also the valuable learning resources for English learning. Besides, the story books in the classroom were related to students’ funds of knowledge, which could raise students’ learning motivation. In addition, during the class observation, the author noticed some strengths and learned great teaching skills of Ms. Levy’s class. On the other hand, based on theories from previous researches and articles, the author also provided some recommendations in order to have students get more benefits in ESL classes.